2014
DOI: 10.1186/1471-2393-14-115
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous ferric carboxymaltose for anaemia in pregnancy

Abstract: BackgroundIron deficiency is a common nutritional deficiency amongst women of childbearing age. Peri-partum iron deficiency anaemia (IDA) is associated with significant maternal, fetal and infant morbidity. Current options for treatment are limited: these include oral iron supplementation, which can be ineffective and poorly tolerated, and red blood cell transfusions, which carry an inherent risk and should be avoided. Ferric carboxymaltose is a new treatment option that may be better tolerated.The study was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 26 publications
6
86
0
4
Order By: Relevance
“…Ferritin values also increased significantly after the infusion. 21 Earlier starting of iron supplementation in these patients, seems to be the most important strategy. 22 David et al, Evstatiev et al and Iftikhar et al [23][24][25] proved that FCM was well tolerated and had better compliance than other iron preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Ferritin values also increased significantly after the infusion. 21 Earlier starting of iron supplementation in these patients, seems to be the most important strategy. 22 David et al, Evstatiev et al and Iftikhar et al [23][24][25] proved that FCM was well tolerated and had better compliance than other iron preparations.…”
Section: Discussionmentioning
confidence: 99%
“…women; 41 studies ), FCM (n = 276 women; four studies 13,[52][53][54] ) and IPM (n = 164 women; three studies [55][56][57] ).…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…The majority of studies involved a comparison group of some kind including oral iron (n = 17; 36%), 11,14,16,19,24,26,27,29,31,32,34,35,37,39,50,56,57 IV iron (n = 4; 9%), 13 [14][15][16]18,20,24,26,28,31,[33][34][35][36][37][38][39]41,42,44,49,50,53 Only one study was identified that directly compared the administration of a full replacement dose of IV iron to a dose that was 300 mg less than the calculated full replacement dose. In comparing the two groups, administration of the full replacement dose was associated with a greater increase of 8 g/L 3-4 weeks after administration and 14 g/L at delivery.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferritin values also increased significantly after the infusion. 9 David et al 10 , Evstatiev et al 11 and Iftikhar et al 12 proved that FCM was well tolerated and had better compliance than other iron preparations.The results of our study were consistent with the above mentioned trials. FCM has been shown to be an effective option in the treatment of IDA in multiple studies and it also improves the quality of life.…”
mentioning
confidence: 99%